CO2, Environmental Emergencies, and Industrial Pollution Assessment in China from the Perspective of the Circular Economy - Zhang, Min; Ren, Fang-rong; Shi, Ying-ying; Chen, Hang-sheng; Tian, Ze (Frontiers in Environmental Science, 2022)
The rise of energy consumption has also increased emissions of the “three wastes” (wastewater, waste gas, industrial solid waste), and environmental emergencies caused by pollutants, natural disasters, and production safety accidents have aroused social concerns. However, as few scholars have combined treatment efficiency of the three wastes with environmental emergencies to explore their relationships, this paper thus uses a two-stage undesirable Data Envelopment Analysis (DEA) method to explore the situations of 4 regions and 30 provinces in China from 2013 to 2017 based on such interactive perspectives. The study finds that the overall regional environmental efficiency in China is generally low. In terms of regional differences, the eastern and northeastern regions are better than the central and western regions. The efficiency values of the three wastes in China has fluctuated greatly from 0.7 to 0.2 in recent years. The efficiency of environmental emergencies in China is greatly affected by the efficiency of environmental governance inputs. Based on the results, the study proposes that the eastern region can be an example for promoting balanced regional development and offers policy recommendations such as taking precautions against environmental emergencies.